Duration of WIC Participation Is Associated with Higher Dietary Quality at 24 Months (P11-048-19). (13th June 2019) - Plank, Kaela; Au, Lauren; Weinfield, Nancy; Borger, Christine; Whaley, Shannon; Berman, Danielle; Ritchie, Lorrene
Abstract: Objectives: This study examined how duration of participation in the Special Supplemental Nutrition Program for Women, Infants, and Children (WIC) is associated with dietary quality at age 24 months using Healthy Eating Index-2015 (HEI-2015) scores. Methods: Data from the WIC Infant and Toddler Feeding Practices Study-2 (WIC ITFPS-2), a longitudinal study on WIC caregivers and their children, was used to examine WIC participation and diet quality. A weighted sample of 407, 416 caregivers (unweighted = 1, 349) from 80 WIC sites nationwide was included. Duration of WIC participation reflects the number of interviews during which caregivers responded that they were receiving WIC benefits (9 interviews occurred between 3 and 24 months). Responses were categorized into low (< 4 interviews), intermediate (5-7 interviews), and high (8-9 interviews) duration groups. Dietary intake was assessed using 24-h dietary recalls administered to caregivers. One-way ANOVA was used to compare average HEI component and total scores by WIC duration. Multivariate linear regression was used to examine independent effects of WIC participation duration on HEI-2015 total score, controlling for maternal race, ethnicity, and education, and household poverty status. Results: The mean total HEI-2015 score of all children at 24 months was 60.5 (SE = 0.4). Total unadjusted HEI-2015 scores were statistically different across WIC duration categories, with more favorable scores among those in the high duration group [Low duration = 55.2 (SE = 1.8), Intermediate duration = 59.2 (SE = 0.8), High duration = 60.9 (SE = 0.4)]. After controlling for sociodemographic factors, high WIC duration was associated with a significantly higher HEI-2015 total score compared with the low WIC duration group (b = 4.06, P  < 0.05). Ethnicity was also significantly associated with total HEI; Hispanic participants had higher mean HEI-2015 scores compared with non-Hispanic Whites (b = 6.25, P  < 0.05). Conclusions: Higher dietary quality was significantly positively associated with WIC duration, as reflected in higher scores for total HEI-2015 and in key categories such as total vegetables, refined grains, and saturated fat. Findings suggest that longer participation in WIC contributes to continued nutritional benefits. Funding Sources: WIC ITFPS-2 is a federally funded study under the direction of the Office of Policy Support in the Food and Nutrition Service, U.S. Department of Agriculture.